PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI ASN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI DAN LINGKUNGAN KERJA SEBAGAI VARIABEL MODERASI) - Ramonzha, Ramonzha; Ichyaudin, Zuhad; Madya, Faisal (JURNAL ILMIAH EDUNOMIKA, 2024)
Government agencies are one of the agencies that get the spotlight in terms of performance. The Regional Secretariat in its implementation is the center of administrative activities of the wheels of government in the region. Human resources are a benchmark for the success of an organization/agency in achieving performance. However, this need will not be sufficient if it is not supported by performance boosters provided by the company and the employees themselves. The boosters are worker competence, compensation, and a good work environment, all of which will increase work motivation. The purpose of this study was to measure the effect of competence, compensation, and work environment on employee performance through work motivation. This type of research is quantitative research with survey methode within questionnaires. The population used was all employees and leaders at the level of the Riau Islands Regional Secretary as many as 183 people and the sample was all levels of employee positions in the Riau Islands Regional Secretariat, namely 100 people. which was determined by census sampling. Then there is no mediating / intervening effect of work environment between competence and work motivation while compensation has an effect to motivation with moderating work environment. However, there is also an effect of compensation and competence on work performance with motivation as intervening variable.